2011
DOI: 10.1590/s0103-166x2011000400006
|View full text |Cite
|
Sign up to set email alerts
|

A diversidade em sala de aula e a relação professor-aluno

Abstract: O presente estudo teve como objetivo identificar as percepções de professores quanto à relação professor-aluno, a partir da aplicação da Escala de Relacionamento Professor-Aluno, versão reduzida e traduzida da Student-Teacher Relationship Scale, relacionando seus domínios a características dos discentes, no que tange às variáveis necessidade educacional especial, sexo, cor/raça, série e idade. Na pesquisa, 21 professoras regentes de seis escolas públicas da cidade de Juiz de Fora, no estado de Minas Gerais, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
(42 reference statements)
3
12
0
5
Order By: Relevance
“…Behavioral issues between students and teachers correspond to one of the main difficulties faced in teaching. Often teachers are unable to handle class behavior, which generates a sense of helplessness and displeasure at work (Barbosa, Campos, & Valentim, 2011;Freitas & Facas, 2013;Gutierréz, 2017;Tostes et al, 2018;Weber, Leite, Stasiak, Santos, & Forteski, 2015). Final grade teachers may suffer greater pressure and demand for results for the accountability of education professionals for student performance (Vieira, Vidal, & Nogueira, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral issues between students and teachers correspond to one of the main difficulties faced in teaching. Often teachers are unable to handle class behavior, which generates a sense of helplessness and displeasure at work (Barbosa, Campos, & Valentim, 2011;Freitas & Facas, 2013;Gutierréz, 2017;Tostes et al, 2018;Weber, Leite, Stasiak, Santos, & Forteski, 2015). Final grade teachers may suffer greater pressure and demand for results for the accountability of education professionals for student performance (Vieira, Vidal, & Nogueira, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although Fakolade, Adeniyi, and Tella (2009) found no relationship between time since training and attitudes of the teachers, Hwang and Evans (2011) indicated that teachers with longer times since training showed more negative attitudes towards inclusion. Barbosa Campos, and Valentim (2011) highlighted that teachers with more experience in the teaching profession presented greater confl ict and less affi nity in relation to the included students because they were more concerned with correcting them than considering them in their specifi cities.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados relativos à rejeição são coerentes com os vários dados apresentados pela literatura internacional e com os poucos da literatura brasileira, que apontam haver uma relação mais conflituosa e menos próxima com os estudantes do sexo masculino e uma interação de maior afinidade com os estudantes do sexo feminino (Baker, 2006;Barbosa et al, 2011;Birch & Ladd, 1997;BolsoniSilva et al, 2013;Jerome et al, 2008;Kesner, 2000;Rudasill & Rimm-Kaufman, 2009;Silver et al, 2005). (Gardinal & Marturano, 2007;Kwok et al, 2007;LaFrance et al, 2003;Maia et al, 2011;Mendez et al, 2002;Stuhlman & Pianta, 2002;Zhou et al, 2009 Sugere-se, a partir das relações apresentadas acima, que os padrões encontrados relativos às proporções de meninas e meninos indicados nas perguntas referentes à aceitação e à rejeição não são fruto das diferenças nas áreas de ensino dos professores ou do maior número de docentes do sexo feminino que constituíram a amostra do presente estudo.…”
Section: Discussionunclassified
“…Isso decorre do fato de que estes comportamentos constituem um desafio para os professores, que não conseguem lidar de forma efetiva com comportamentos antissociais e agressivos, atitudes desafiadoras, desobediência, hiperatividade e falta de concentração nas tarefas, tornando difícil a organização da sala de aula e o processo de ensino (Baker, 2005;Barbosa, Campos, & Valentim, 2011;Buyse et al, 2008;Del Prette & Del Prette, 2001;LaPointe, 2003;López, 2004;Marinho, 2003).…”
Section: Problemas De Comportamentounclassified
See 1 more Smart Citation